Economic value added zur Prognose der Performance europäischer Aktien - Thomas Heidorn; Hans-Dieter Klein; Frank Siebrecht (Hochschule für Bankwirtschaft (HfB), 2000)
This paper shows that Economic Value Added (EVA) can be used to optimize the performance of european share investements. Investing in the top third relative EVA performers, leads to a significant outperformance. This is true for market and sektor investments. The best results were found for growth and technology. On the individual firm level the results are less convincing. For individual shares a large (>2,5%) positive EVA is a good indicator for outperformance.
urn:nbn:de:101:1-2008071617
Keywords: 330